Factors Associated With Missed Opportunities for Influenza Vaccination - Djeneba Audrey Djibo; K. Michael Peddecord; Wendy Wang; Kimberly Ralston; Mark H. Sawyer (SAGE Publishing, 2015)
Objective: Annual influenza vaccination rates remain well below health objectives. Most primary care clinic visits present opportunities for vaccination. The purpose of this study was to quantify missed opportunities (MOs) during the entire influenza season. Patients and clinic characteristics associated with vaccination and MOs are identified. Methods: Influenza vaccinations recorded in random chart reviews of children 6 months to 5 years and of adults 50 years and older at 6 pediatric and 7 adult primary care clinics were assessed during the 2010-2011 influenza season. Patient-specific MOs accounted for variable timing and number of visits throughout the vaccination season. Data were assessed using descriptive, graphical, proportional hazards regression methods. Results: Data for 1136 children and 1329 adults were analyzed. By the end of the season, influenza vaccination coverage recorded in medical records reached 56% and 26% for children and adults, respectively. MOs are common throughout the season and rise sharply after December. By the end of the season, 30.2% of children and 44.9% of adults had 2 or more MOs. Characteristics associated with MOs included age, insurance type, number of visits, and type of medical practice. Conclusions: Missed opportunities abound, especially after December. Strategies targeting patients most likely to have MOs and encouraging the use standing orders, reminders, and monitoring in order to reduce them need to be sustained.